Symphonic Vision Evening Glow by Juris Karlsons in the Context of Regional Identity - Vecumnieks, Andris (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2012)
The purpose of this work is to define the significance of the symphonic vision Vakarblāzma (Evening Glow) by Juris Karlsons in the context of regional identity and to indicate the special place of this opus in the music literature of Latvia and the world. The main objectives of the work are to describe and to define the search for national and regional identities in Latvia and in the world as well as to analyse the symphonic vision Vakarblāzma by Juris Karlsons according to the aforementioned descriptions, placing emphasis on the analysis of the unique and individual approaches of the author within the context of common and universal solutions. The main employed methods are the historic analysis of the issue and the empirical analysis, in many cases based on the experiences and personal views of the author Juris Karlsons, expressed in recorded conversations and interviews from 2010 to 2012 (author owns these recordings and retains full rights). Main conclusion – the search for national and regional identity takes place on regular basis in cyclic and spiralled manner, marking new indicators of national identity for every epoch; the unique significance of J. Karlsons is an indicator that permits universal mobility and substitutability.